Kajian Hukum Hilirisasi dan Penghentian Ekspor Mineral Logam - Siombo, Marhaeni Ria (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
Indonesia is one of the countries that has large reserves of various minerals in the world. In addition to metal minerals such as coal, nickel, etc., which are used for export, currently the government has made it mandatory to downstream metal minerals in the country. In addition, the potential for metal minerals in Indonesia also plays a role in increasing investment for state revenue, through smelter investments. Through the policy of prohibiting the export of metal mineral ores, the continuity of the supply of raw metal minerals in the long term for the needs of domestic smelters is maintained. But there are issues in society due to the export ban affecting the selling price of metal minerals, especially impacting business activities. This paper discusses the extent of metal mineral investment policies, the ban on metal mineral ore exports, downstreaming, and the obstacles faced. The author found that downstream metal minerals actually pushed metal mineral prices in a positive direction, thus encouraging investors to come to Indonesia